2016
DOI: 10.5539/cis.v9n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Technology Aspects of E-Government Readiness in Developing Countries: A Review of the Literature

Abstract: The rapid global growth of the Internet and information technology has inspired many governments to transform their traditional services into electronic ones. Many governments are now developing, implementing and improving their strategies to transform government services using information and communication technologies (ICTs). E-Government, as it is known, has become a popular focus of government efforts in many developed countries and, more recently, in several developing countries. Further, e-government ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The other example is the police facility and the renewal of the driving license or vehicle registration services across the Internet to get the police administrative apparatus to the car owners and drivers' group. Those involved do not have to think about the office to get services (Erhan et al, 2017;Mi'rojul & Yunas, 2016;M. Baeuo et al, 2016;Nurita, 2016;Witarsyah et al, 2017).…”
Section: A Critical Approach To Information and Communication Technolmentioning
confidence: 99%
See 2 more Smart Citations
“…The other example is the police facility and the renewal of the driving license or vehicle registration services across the Internet to get the police administrative apparatus to the car owners and drivers' group. Those involved do not have to think about the office to get services (Erhan et al, 2017;Mi'rojul & Yunas, 2016;M. Baeuo et al, 2016;Nurita, 2016;Witarsyah et al, 2017).…”
Section: A Critical Approach To Information and Communication Technolmentioning
confidence: 99%
“…The implementation of electronic government (e-Government) in Indonesia and what has been accomplished so far undoubtedly need change on both sides in terms of the implementation plan and the philosophy of e-Government. The delay in E-Government progress would only ensure that this country is far from changing the values, enhancing the standard of public services for all, and eventually preventing societal welfare Farida et al, 2020;Baeuo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] [17] show how Cloud Computing can refine the existing eGovernment readiness indices; so that indicators like ICT infrastructure and human capital get less weight, while indicators such as connectivity and regulations acquire more weight. [1] claim that The survey demonstrated that there is an absence of examination and assertion about the factors that shape the technological aspects of eGovernment readiness; hence, a clear gap is distinguished as existing in the current knowledge on the technological aspects of eGovernment readiness. [18] highlighted that the result reveals that the respondents' rating of their access to ICT is low.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…In these situations, technology plays a key role in services so as to enhance eGovernment infrastructure. eGovernment has become a global issue having a significant influence on all public sectors and economies; hence, there is a need for global cooperation as well as knowledge and experience exchange [1]. New technologies facilitate collaboration between people.…”
Section: Introductionmentioning
confidence: 99%